Causal model of decision-making for type 2 diabetes mellitus patients regarding self-management - Amin Rais, Muhammad; Dini, Mitha Permata; Supriyanto, Stefanus (Science Midwifery, 2024)
Indonesia faced a 49.9% mortality rate in 2019 due to diabetes mellitus, predominantly Type 2 DM, accounting for over 90% of cases. This type of diabetes, often complicated, stands as a leading cause of death in the country. Managing Type 2 DM necessitates medical care and self-management education to prevent long-term complications. Effective strategies encompass education, nutritional therapy, exercise, and pharmacological treatment, reliant on adherence, knowledge, and self-awareness. The doctor-patient relationship significantly influences adherence, emphasizing the need for enhanced decision-making frameworks. This study, employing an analytic observational approach with 99 respondents, explores decision-making models for Type 2 DM self-management in primary and secondary healthcare settings. Results from Partial Least Squares (PLS) analysis indicate patient (0.253), doctor (0.344), and family (0.312) factors influencing decision-making, which, in turn, impacts self-efficacy (0.330). Family dynamics strongly correlate with self-efficacy (0.550), further impacting self-management (0.679). Recommendations advocate shared decision-making, emphasizing disease knowledge, patient involvement in treatment planning, adequate consultation time, and increased family participation to bolster self-efficacy and self-management in Type 2 DM patients.